The impacts from Sr4La(PO4)3O: Ce3+, Tb3+, Mn2+ phosphor resulting in luminous flux of WLED devices - Huu Phuc Dang; Bui Van Hien; Nguyen Le Thai (Institute of Advanced Engineering and Science, 2022)
Using the solid-state technique that involves great temperature, we created multiple phosphors Sr4La(PO4)3O:Ce3+, Tb3+, Mn2+ (abbreviated as SLPO:Ce, Tb, Mn). We then examined their heat consistency, luminescence, as well as energy shift from Ce3+ to Tb3+ and Mn2+. We can acquire a considerable boost for the faint emission in green generated by Tb3+ as well as the emission in red generated by Mn2+ via adding the sensitizer Ce3+ ions. Through modifying the proportion between Ce3+ and Tb3+ along with the proportion between Ce3+ and Mn2+, it is possible to adjust the chroma of emission. We acquired white illumination which had color coordinates determined as (0.3326, 0.3298) for the testing phosphor Sr4La(PO4)3O: 0.12Ce3+, 0.3Mn2+. Such result displays the promising efficiency of phosphors Sr4La(PO4)3O:Ce3+, Tb3+, Mn2+ for the WLED devices.